Aplikasi Absensi Digital dengan Fitur Reward Ekslusif Otomatis untuk Meningkatkan Kedisiplinan Kinerja Guru Pendidikan Anak Usia Dini: A Digital Attendance Application with an Exclusive Automatic Reward Feature to Improve Early Childhood Education Teacher Performance Discipline - Virania Kusuma Dewi; Assyifa Dhian Dhani; Rasiyah Zahratun Nadhifah; Fetty Ernawati (Litera Academica Publishing, 2026)
Technological advances have significantly impacted various aspects of human life. Especially in education, numerous innovations have been implemented, including in the management of educational staff to improve teacher discipline. Improving teacher discipline is achieved through the use of digital attendance applications to facilitate principals' supervision. However, because these applications are developed by each region, the existing features are very different, and there is no feature to provide motivation for teachers. Therefore, innovation is needed in the form of a reward feature, which can take the form of webinars or specific competency training for teachers who maintain 100% attendance. This research method uses a literature study by analyzing journals, books, and previous research. The purpose of this study is to determine changes in teacher discipline after the introduction of the exclusive reward feature. This research is able to contribute theoretical updates in the field of educational staff management with the innovative concept of providing rewards for teachers who are able to discipline themselves in carrying out digital attendance.